Pharmaco-fUS in cognitive impairment: Lessons from a preclinical model. (November 2022) - Vidal, Benjamin; Pereira, Mickaël; Valdebenito, Marco; Vidal, Louis; Mouthon, Franck; Zimmer, Luc; Charvériat, Mathieu; Droguerre, Marine
Background: There is an urgent need to understand and reverse cognitive impairment. The lack of appropriate animal models combined with the limited knowledge of pathophysiological mechanisms makes the development of new cognition-enhancing drugs complex. Scopolamine is a pharmacologic agent which impairs cognition and functional imaging in a wide range of animal species, similarly to what is seen in cognitive impairment in humans. Methods: In this study, using a functional ultrasound (fUS) neuroimaging technique, we monitored the impact of donepezil (DPZ), a potent acetylcholinesterase inhibitor and first-line treatment in patients with mild to moderate Alzheimer's disease, in a scopolamine-induced mouse model. Results: We demonstrated that despite its low impact on the cerebral blood volume (CBV) signal, scopolamine injection produced an overall decrease in functional connectivity between various brain areas. In addition, we revealed that DPZ induced a strong decrease in CBV signal without causing a difference in functional connectivity. Conclusion: Finally, our work highlighted that DPZ counteracted the impact of scopolamine on functional connectivity changes and confirmed the interest of using pharmaco-fUS imaging on cognitive disorders, both in frequent and rare neurological disorders.